2022
DOI: 10.1186/s40360-022-00571-9
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin versus placebo on estrogen levels in postmenopausal women: a double-blind randomized controlled clinical trial

Abstract: Background Estrogen is involved in the pathogenesis of breast and gynecological cancers. Regular use of aspirin reduces estrogen levels. The present study aimed to evaluate the effect of aspirin on estrogen levels in postmenopausal women. Methods This double-blind, placebo-controlled parallel-group trial was conducted on postmenopausal women referred to an outpatient clinic at a women’s hospital in Tehran. Volunteers were randomly assigned to recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Recent studies have found that in addition to its anti-inflammatory and cardioprotective characteristics, it serves a role in modulating BC risk [9] . Its ability to prevent cancer is mediated by its ability to reduce cell proliferation, induce apoptosis, and modify lymphangiogenesis [10] . Although the precise method by which aspirin exerts its protective effects on BC is not entirely understood the fundamental mechanism could be explained by suppressing cyclooxygenases (COXs), particularly COX-2, whose overexpression is associated with lymph node metastases, larger tumor sizes, and worse prognoses [10] .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have found that in addition to its anti-inflammatory and cardioprotective characteristics, it serves a role in modulating BC risk [9] . Its ability to prevent cancer is mediated by its ability to reduce cell proliferation, induce apoptosis, and modify lymphangiogenesis [10] . Although the precise method by which aspirin exerts its protective effects on BC is not entirely understood the fundamental mechanism could be explained by suppressing cyclooxygenases (COXs), particularly COX-2, whose overexpression is associated with lymph node metastases, larger tumor sizes, and worse prognoses [10] .…”
mentioning
confidence: 99%
“…Its ability to prevent cancer is mediated by its ability to reduce cell proliferation, induce apoptosis, and modify lymphangiogenesis [10] . Although the precise method by which aspirin exerts its protective effects on BC is not entirely understood the fundamental mechanism could be explained by suppressing cyclooxygenases (COXs), particularly COX-2, whose overexpression is associated with lymph node metastases, larger tumor sizes, and worse prognoses [10] . COX-2 suppression inhibits prostaglandin synthesis, which lowers estrogen levels.…”
mentioning
confidence: 99%
See 3 more Smart Citations